2015
DOI: 10.1080/01431161.2015.1072650
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring surface water content using visible and short-wave infrared SPOT-5 data of wheat plots in irrigated semi-arid regions

Abstract: Irrigated agriculture is an important strategic sector in arid and semi-arid regions. Given the large spatial coverage of irrigated areas, operational tools based on satellite remote sensing can contribute to their optimal management. The aim of this study was to evaluate the potential of two spectral indices, calculated from SPOT-5 highresolution visible (HRV) data, to retrieve the surface water content values (from bare soil to completely covered soil) over wheat fields and detect irrigation supplies in an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 51 publications
1
17
0
1
Order By: Relevance
“…This conforms with results obtained in Kalubarme and Sharma (2015) where NDWI values were observed to be sensitive to stress conditions in wheat-cultivated farm plantations. Similarly, results obtained by Benabdelouahab et al (2015) also showed that MSI and NDWI are sensitive indicators of stress also in a wheat-cultivated farm field. However, the near-infrared and shortwave infrared bands were also observed to have the highest contribution in splitting oil contaminated and oil-free grassland landcover scheme.…”
Section: Resultssupporting
confidence: 60%
“…This conforms with results obtained in Kalubarme and Sharma (2015) where NDWI values were observed to be sensitive to stress conditions in wheat-cultivated farm plantations. Similarly, results obtained by Benabdelouahab et al (2015) also showed that MSI and NDWI are sensitive indicators of stress also in a wheat-cultivated farm field. However, the near-infrared and shortwave infrared bands were also observed to have the highest contribution in splitting oil contaminated and oil-free grassland landcover scheme.…”
Section: Resultssupporting
confidence: 60%
“…In Morocco, numerous studies have highlighted the potential use of remote sensing data in representing and monitoring different biophysical parameters (Ezzine et al 2015). These include traditional land cover maps and digital elevation models, as well as snow cover (Marchane et al 2015;Schulz and De Jong 2004), surface temperature (Boudhar et al 2011), near-surface soil moisture (Benabdelouahab et al 2015;Eweys et al 2017), evapotranspiration (ET) (Akdim et al 2014), precipitation (Ouatiki et al 2017), and snowmelt runoff (Boudhar et al 2009).…”
mentioning
confidence: 99%
“…In the study area, the soils are classified as isohumic, mainly based on French soil classification (CPCS) (Massoni et al, ; Badraoui and Stitou, ). From 30 soil samples collected from several sites providing coverage of the entire study area, soil physics properties were measured (Benabdelouahab et al, ). For three depths (0–30 cm), (30–60 cm) and (60–90 cm), permanent wilting point (PWP) and field capacity (FC) were determined using a pressure plate extractor.…”
Section: Methodsmentioning
confidence: 99%
“…Crops in semi‐arid regions, such as those in Morocco, regularly face water stress, considered the main limiting factor for crop growth. There is therefore a need to assess soil water availability in order to improve irrigation scheduling and prevent water stress adversely affecting yield (Benabdelouahab et al, ).…”
Section: Introductionmentioning
confidence: 99%